Effect of tree roots on heavy rainfall-induced shallow landslides - Yunzhao Lin; Wenbin Jian; Yilong Wu; Zuteng Zhu; Hao Wang; Hongqiang Dou; Zengrong Lai (Geomatics, Natural Hazards & Risk, 2024)
To investigate the influence of tree roots on the triggering mechanism of shallow landslides, this study focused on a typical vegetation-covered cluster landslide in the Wuping area of China. A tree root profile investigation and a double-ring infiltration test were conducted. The undisturbed soil samples were collected for laboratory tests to measure the influence of tree vegetation on soil physical and hydraulic properties. The root reinforcement effect is limited by the depth of root distribution, with over 90% of the roots situated above the slip surface. The presence of roots increases the resistance of the soil to disintegration. The soil disintegration in the 0–80 cm layer was less than 25% after 24 h of water immersion and the soil undergoes complete disintegration at a depth of 180–200 cm within 120 s. Tree roots facilitate the infiltration of soil, and Ks at 0 m was 11.21 times than that at 2 m, and the interface between soils with roots and soils without roots may become a sliding surface. Under extreme rainfall conditions, the root system promotes water infiltration, accelerates the softening and disintegration of the soil on the sliding surface, which adversely affects the stability of landslides.